MANAGEMENT AUDIT AS AN INSTRUMENT TO ASSESS THE EFFECTIVENESS OF HUMAN RESOURCE FUNCTION (CASE STUDY ON ISLAMIC HOSPITAL OF UNISMA MALANG) - Fernando Ivan Lukmana Haryanto; Akie Rusaktiva Rustam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Management audit of human resources conducted at Islamic Hospital of Unisma Malang aims to determine the effectiveness of human resources functions organized by the hospital, to determine the effectiveness of achieving the hospital's objectives of policies and procedures of human resource functions in Islamic Hospital of Unisma Malang, and to identify bottlenecks in the implementation of the human resource function as well provide recommendations on the obstacles encountered. The method used in this research is descriptive method. The data source were obtained by conducting interviews, documentations, and observations. The data analysis was implemented by comparing three basic elements of management audit, such as criteria, cause, and effect. Data analysis was conducted by comparing the three basic elements of management audit, such as the criteria, causes, and effect. The research problem is limited on the human resources function organized by the Islamic Hospital of Unisma Malang, which are human resource planning, labor recruitment, labor selection, orientation and placement, education and training, career planning and development, performance appraisal, granting of compensation and reward, manpower protection, and termination of employment. The result showed, that the human resource planning, labor recruitment, labor selection, orientation and placement, career planning and development, performance appraisal, granting of compensation and reward, manpower protection, and termination of employment has been run effectively, yet education and training function is not operating effectively. Keywords: Management Audit, Effectiveness, Human Resources.